An Ontological Approach to Smart Packaging Based on Agricultural Waste - Hanifah Ayu; M Sarjan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Food packaging is transitioning from a passive protective function to an intelligent system (smart packaging) capable of integrating, responding to, and communicating food conditions in real time. The dominance of petroleum based plastics in the packaging industry has serious environmental and health impacts, triggering the search for more sustainable alternative materials. This study uses an ontological approach to define agro-waste as an essential resource rich in biopolymers and bioactive compounds, making it a strategic raw material for smart packaging. Functionally and sustainably, this material is processed into active (antioxidant, antimicrobial) and intelligent (sensor/indicator) packaging components that effectively extend shelf life, reduce food waste and food loss. From a stakeholder perspective, the integration of agro waste based smart packaging aligns with circular economy principles as it transforms low value organic residues into high value packaging products and supports the achievement of the SDGs related to sustainable consumption. Overall, the ontological approach provides a framework for shifting the perspective of waste, validating material performance, and guiding research strategies to overcome technical and regulatory barriers, in order to realize the implementation of agro waste based smart packaging in the food industry.